Avaliação de procedimentos de ensino para ampliar a produção oral de sentenças em crianças com implante coclear - Neves, Anderson Jonas das (2019)
Researches in verbal learning of sentences, in cochlear implants’ (CI) users, are recent and suggest the potential of equivalence-based instruction (EBI) and matrix training to promote the symbolic relations, the control by minimal units, the speech accuracy and the verbal productivity, from a minimum set of sentences directly taught. These studies encourage more systematic investigation to explore teaching procedures and contents, aiming at the proposing a curriculum to establish a solid verbal repertoire in children with CI. The present dissertation contributed in this direction with four studies. Study 1 evaluated the effects of two errorless teaching procedures (exclusion and fading out of the visual component in sample) on the learning of the conditional relations between dictated sentences and pictures, the equivalence relations, the recombinative generalization and the speech accuracy in tact, in six children with CI who were readers. The sentences were organized into two matrices (Sets 1 and 2) with nine sentences each; three were directly taught (the diagonals), and six were evaluated in generalization probes. The teaching conditions (fading out and teaching by exclusion) were counterbalanced among the participants, and verbal relations of the two sets were probed in multiple baseline across sets. The EBI included the tasks of the selection of pictures by matching-to-sample (MTS), with teaching by exclusion or fading out; and the tasks of the construction of printed sentences by constructed-response matching-to-sample (CRMTS), conditionally to dictated sentences. Both procedures established conditional relations between dictated sentences and pictures, but the teaching by exclusion generated fast learning and with less errors. Five of the six participants formed equivalence relations, improvement the speech accuracy in picture tact and showed recombinative performances with words of taught sentences. Study 2 simulated a curriculum module, with three sets of sentences, with progressive levels of difficulty (sentences with regular and irregular words, and pseudo-sentences); and six children with CI, readers and who have inaccurate tacts were exposed to this module. The EBI was the same as Study 1 and incorporated teaching by exclusion (more effective). According to probes in multiple baseline, all participants learned the taught relations, increased the accuracy speech in tact, and demonstrated both semantic (symbolic) and syntactic (intra and inter-matrices, receptive and expressive) productivy in the three sets of sentences. Study 3 used the EBI to teach sentences in second language and evaluated the formation of equivalent stimulus classes in Portuguese, class expansion for English sentences, and emergence of verbal operants, for three children with CI and previously readers. Participants learned to select pictures and written sentences, conditionally to dictated sentences, in Portuguese and in English, by MTS and exclusion procedures. They formed equivalence classes in Portuguese, expanded classes for sentences in English and showed accuracy in English-to-Portuguese oral translation; however, oral production in the echoic, reading and tact in English, and in the Portuguese-to-English intraverbal remained inaccurate. Study 4 evaluated whether the teaching of simple discriminations using written pseudo-sentences and abstract figures, with specific consequences formed by dictated pseudo-sentences and representative pictures, would promote the emergence of conditional and symbolic relations, with pseudo-sentence, for three children with CI. Three participants learned the simple discriminations, and conditional and equivalence relations were consistent for two participants. The findings of four studies show teaching conditions that were effective to generate the relational and symbolic learning, the speech accuracy in tact, and verbal productivity of sentences, for children with CI. These teaching procedures and contents may have implications both teaching and auditory habilitation/rehabilitation.